Accounts payable best practices - Schaeffer, Mary S. (John Wiley & Sons, Inc., 2004)
Accounts Payable Best Practices provides businesses and other organizations with a strong sense of where they stand against industry leaders and shows them how to take their services and organizational processes to state-of-the-art levels. Documented strategies and tactics employed by highly admired companies are presented--both successful and unsuccessful--to illustrate the real-world functionality of each process and approach. Every chapter features a brief explanation of the process or topic being addressed to accompany the discussion of best practices. However, for a variety of reasons, some firms aren’t in a position to employ best practices. To bridge the gap between the latest theory and practice, Accounts Payable Best Practices identifies "Almost Best Practices." These special sections consider that not all practices will work at every company, and they offer successful alternatives to best practices. Also included are discussions on practices that absolutely should not be used, but may be practiced at other companies.